PERAN GURU DALAM PROSES BELAJAR SISWA - eep saepul; Annur Safarnaa (MGMP PAI Jawa Barat, 2022)
Teachers play an important role in the implementation of educational plans at the school level. This role is sometimes challenged by the level of teacher efficiency in performance where educational resources are scarce. Teachers face the challenge of optimally utilizing available resources in generating maximum output. The main purpose of conducting research at this very local and practical level is to instill a scientific mindset in teachers. From its professional development in relation to the change of the individual as a professional and the protagonist of education also in the dimension of the change of the school as an organized educational institution. This makes us know that our problem or concern focuses on: the teacher as a personality, the teacher's attitude towards the student, his style and way of working, the strategies and methodologies teaching. Therefore his professionalism and the level of moral preparation should be pleasant so that he can successfully complete his work. If we look at the development of schools and the role of teachers historically, we see that the functions and roles of teachers have changed along with changes in society, as schools go on.